Developing of New Facets of Indirect Modeling in the Geosciences - Ghaffari, H.; Shakeri, H.; Sharifzadeh, Mostafa (n/a, 2009)
In this paper, we describe some applications of Self Organizing feature map Neuro-Fuzzy Inference System(SONFIS) and Self Organizing feature map Rough Set (SORST) in the analysis of permeability at a dam site and lost circulation in the drilling of three wells in Iran. Elicitation of best rules on the information tables, exploration of the dominant structures while they take a balance state with the second granulation level (rules) and highlighting of most effective attributes (parameters) on the selected systems, are some of the benefits of the proposed methods. In the other process, using complex network (graph) theory - as another method outside of 1:1 modelling category- mechanical behaviour of a rock joint has been investigated.